Quantifying stroke coordination during the breathing action in front-crawl swimming using an instantaneous net drag force profile - Formosa, D. P.; Sayers, M. G. L.; Burkett, B. (Journal of Sports Sciences, 2015)
This study used both an instantaneous net drag force profile and a symmetry timing to evaluate the effect of the breathing action on stroke coordination. Twenty elite swimmers completed a total of six randomised front-crawl towing trials: (i) three breathing trials and (ii) three non-breathing trials. The net drag force was measured using an assisted towing device mounted upon a Kistler force platform, and this equipment towed the swimmer at a constant speed. The net drag force profile was used to create a stroke symmetry index for each swimming trial. Analysis using the symmetry indices identified that the majority of participants demonstrated an asymmetrical instantaneous net drag force stroke profile in both the breathing and non-breathing conditions, despite no significant differences in the time from finger-tip entry to finger-tip exit. Within the breathing condition, the faster swimmers compared to the slower swimmers demonstrated a lesser percentage of overlap between stroke phases on their breathing stroke side. During the non-breathing condition, the faster participants compared to the slower swimmers recorded a reduction in the percentage of overlap between stroke phases and less duration in the underwater stroke on their breathing stroke side. This study identified that the majority of participants demonstrated an asymmetrical net drag force profile within both conditions; however, asymmetry was less prevalent when examining with only the timing symmetry index.